PENGARUH EFEKTIVITAS IKLAN TERHADAP CITRA MEREK SERTA DAMPAKNYA PADA MINAT BELI SAMPO PANTENE (Studi pada Mahasiswi Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Haerani, Yeni; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2015)
Pantene is a famous brand shampoo ofÂ Â PT. Protect Gamble. Pantene is the market leader of category shampoo during the past four years. However, Pantene shampoo decreased brand value, which means a decline in the performance of the brand. It is characterized by the decrease TOM Brand, TOM Advertising and Brand Share. Pantene as a market leader need to be careful because it can lower the buying interest Pantene shampoo.This study aims to determine the effect of the effectiveness of advertising on brand image as well as its impact on buying interest Pantene shampoo. This study uses five variables: the celebrity endorser, the appeal of advertising, advertising effectiveness, brand image and purchase interest. Research hypothesis testing using the data of 200 respondents.The analysis technique used in this research is Structural Equation Model (SEM) of 21.0 AMOS program.Research shows that in order to increase interest in buying Pantene shampoo can through 4 process. However, the most influential of the increased interest in buying shampoo Pantene is the appeal of advertising that influence the effectiveness of advertising as a determinant of success in increasing buying interest.